PENGARUH METODE CIRCUIT TRAINING TERHADAP PERSENTASE LEMAK WANITA USIA DEWASA (19-44 TAHUN) MEMBER ATLAS SPORTS CLUB KOTA MALANG - Yudhestira Varid Avtaviriga; Olivia Andiana (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The problem of high body fat percentage in adult women is exacerbated by hormonal fluctuations, high-calorie dietary habits, and confusion in choosing the appropriate physical exercise to achieve body goals. Circuit training was chosen as an alternative because it combines aerobic and resistance exercises in a structured, time-efficient series that can maximize energy expenditure. This quasi-experimental study employed a one-group pre-test post-test design involving 15 women aged 19–44 years from Atlas Sports Club, Malang City, who underwent a four-week circuit training program. Body fat percentage was measured before and after the intervention, and the data were analyzed using the Shapiro-Wilk test and Paired Sample T-Test. The results showed a mean decrease in body fat percentage of 1.81% with p = 0.012 (p < 0.05), indicating that circuit training has a significant effect and can be recommended as a relevant exercise for adult women to achieve measurable body goals.